Judge's Ex Officio Authority in Sharia Economic Dispute Resolution Without The Presence of The Defendant Civil Procedural Law Perspective - Ais, Afifah Rohadatul; Nahidloh, Shofiyun (Et-Tijarie, 2025)
In the procedural law system applicable in the judicial environment, there is an ex officio right. In this case, a judge can determine a policy on a decision that is considered good and fair because of his position. Law No. 48 of 2009 emphasizes that courts must adjudicate without discrimination and are obliged to assist those seeking justice. This study aims to determine the ex officio authority of judges in resolving sharia economic disputes without the presence of the defendant from a civil law perspective, using case study 1716/Pdt.G/2024/PA.Bjn. This study is a descriptive qualitative research with an empirical legal approach. The primary data source used is interview data from the panel of judges and the deputy court clerk in case 1716/Pdt.G/2024/PA.Bjn, while the secondary data source is obtained from a list of references related to the material to be analyzed, namely legal documents such as laws, regulations, and court decisions. The findings of this study indicate that judges conduct trials using their ex officio authority to ensure legal effectiveness and certainty, particularly in regulating the execution of collateral objects that are not explicitly requested in the petition. Nevertheless, the judge's actions remain consistent with the principles of civil procedure law, including legal certainty, justice, and judicial proactivity within the boundaries of the authority granted. The exercise of ex officio authority demonstrates that in matters of Islamic economics, judges are not only bound by the reasons stated in the complaint but also tasked with formulating effective and enforceable decisions.